Network Authentication Protocol Based on Secure Biometric NIDN - Muntasser S. Falih; Fatima B. Ibrahim; Mahmood K. Ibrahem (Iraqi Journal of Science, 2021)
In this paper an authentication based finger print biometric system is proposed with personal identity information of name and birthday. A generation of National Identification Number (NIDN) is proposed in merging of finger print features and the personal identity information to generate the Quick Response code (QR) image that used in access system. In this paper two approaches are dependent, traditional authentication and strong identification with QR and NIDN information. The system shows accuracy of 96.153% with threshold value of 50. The accuracy reaches to 100% when the threshold value goes under 50.